IMPLEMENTASI IKRAR TAUKIL WALI DALAM PERATURAN MENTERI AGAMA NO 20 TAHUN 2019 DI KANTOR URUSAN AGAMA KABUPATEN KUTAI TIMUR - Hidayat, Rahman; Iswanto, Bambang; Haries, Akhmad (JAS : Jurnal Ahwal Syakhshiyyah, 2023)
KUA(religious Affairs office) Sangatta Utara and KUA (religious Affairs office) Bengalon are the KUA (religious Affairs office) with the highest number of marriage events, of course this high number also influences the problems that occur, especially for bridal couples who are getting married but their guardians are not present or are absent Minister of Religion Regulation No. 20 of 2019 concerning the vows of guardians If the guardian cannot attend the ceremony, he must make a guardian's pledge at his domicile, this is to avoid falsifying the guardian's data or other unlawful actions. The aim of this research is to find out and analyze the implementation of the taukil wali pledge in the Minister of Religion Regulation No. 20 of 2019 in the KUA of East Kutai Regency and identify supporting and inhibiting factors. The research method is qualitative with a Field Research type of research with a sociological-juridical approach. The data collection techniques are observation, interviews and documentation, the data analysis techniques used are first data condensation, then data presentation and finally drawing conclusions from the data, as well as using data validity techniques. The results of the research are that KUA Sangatta Utara and KUA Bengalon have implemented it in accordance with PMA Number 20 of 2019, KUA Sangatta Utara and KUA Bengalon postponed bridal couples whose guardians were unable to attend the ceremony and without having a guardian's vows, although there were some who still carried out the ceremony even without However, the guardian's pledge was still forced to be done because the guardian could not be contacted and the family had insisted and the travel distance was more than 92.5 km so it was automatically transferred to the judge's guardian. The inhibiting factor is that the community lacks socialization and another obstacle is the lack of solidarity between KUAs. The supporting factor in North Sangatta KUA and Bengalon KUA is that the employees have a patient spirit, so that whatever problems can be resolved well and support from the Regency Ministry of Religion which continues to monitor and provide support. in order to implement the PMA well.   Keywords: Implementation, Pledge of Taukil Wali, PMA Number 20 of 2019